Nursing older people : realities of practice - Heather Elbourne; Andrée Le May (Oxon : Routledge, 2020)
This practical guide helps student and practising nurses to understand the impact of their care when working with older people. With stories from older people who have had varied experiences of health care and nursing, chapters are underpinned by five key principles: providing patient-centered and dignified care, shared decision-making involving family and friends, multidisciplinary care, improving well-being through companionship and a sense of value, and an appreciation of both the challenges and rewards of working with older people. This book offers: Stories which reflect the complexity of care and health experienced by older people and their journeys. Topic-oriented chapters which provide a series of evidence-based readings which use the most up-to-date research evidence merged with national and international policy and practitioner experience. Practical tips and key messages for working with older people. The volume canbe used to help nursing students and practising nurses to understand better how their care might impact positively on older people's health and well-being. This situates the reader within the world as experienced by older people
Keywords: Aged psychology; MEDICAL Allied Health Services General; Geriatric Nursing methods; Aging